THE EFFECT OF MASS OF COAL FLY ASH-CHITOSAN COMPOSITE PELLETS MODIFIED WITH GLUTARALDEHYDE ON THE ADSORPTION OF MERCURY IN SOLUTION - Syauqiah, Isna; Utami, Umi Baroroh Lili; Yusniar, Meina Wulansari (TROPICAL WETLAND JOURNAL, 2017)
Fly ash can be used and utilized as an adsorbent because it is cheap and effective to adsorb waste in the aquatic environment. Hg also known as Mercury is a carciogenic heavy metal and potentially threatens human health at very low concentrations. In this study, fly ash was applied as the adsorbent for Hg2+ in the form of chitosan-fly ash composite pellet and was cross-linked with glutaraldehyde in order to know how much the mass of pellets that can be used to lower the concentration of Hg2+ in solution. The results showed that the fly ash can be compositated with chitosan gel after going through the process of physical-chemical activation so that it can be formed into adsorbent pellets/granules. The optimum condition was obtained from adsorbent pellets of fly ash-chitosan composite crosslinked with glutaraldehyde after contacted with a solution containing Hg2+ with the pellet mass of 3 g.Keywords: composite, fly ash, glutaraldehyde, pellets